Sed1p Is a Major Cell Wall Protein of Saccharomyces cerevisiae in the Stationary Phase and Is Involved in Lytic Enzyme Resistance - Shimoi, Hitoshi (American Society for Microbiology, 1998)
A 260-kDa structural cell wall protein was purified from sodium dodecyl sulfate-treated cell walls of Saccharomyces cerevisiae by incubation with Rarobacter faecitabidus protease I, which is a yeast-lytic enzyme. Amino acid sequence analysis revealed that this protein is the product of the SED1 gene. SED1 was formerly identified as a multicopy suppressor of erd2, which encodes a protein involved in retrieval of luminal endoplasmic reticulum proteins from the secretory pathway. Sed1p is very rich in threonine and serine and, like other structural cell wall proteins, contains a putative signal sequence for the addition of a glycosylphosphatidylinositol anchor. However, the fact that Sed1p, unlike other cell wall proteins, has six cysteines and seven putative N-glycosylation sites suggests that Sed1p belongs to a new family of cell wall proteins. Epitope-tagged Sed1p was detected in a β-1,3-glucanase extract of cell walls by immunoblot analysis, suggesting that Sed1p is a glucanase-extractable cell wall protein. The expression of Sed1p mRNA increased in the stationary phase and was accompanied by an increase in the Sed1p content of cell walls. Disruption of SED1 had no effect on exponentially growing cells but made stationary-phase cells sensitive to Zymolyase. These results indicate that Sed1p is a major structural cell wall protein in stationary-phase cells and is required for lytic enzyme resistance.